STRATEGI PENDIDIK DALAM MELATIH KEDISIPLINAN SHOLAT BERJAMAAH MELALUI PROGRAM PELAYAN TAMU ALLAH - Pratama, Yona Anis; Romadlon, Dzulfikar Akbar (PAI RAFAH, 2024)
This study aims to determine the strategy in training the discipline of congregational prayers of students through the Allah's Guest Servant Program (PTA) at SMA Insan Cendekia Mandiri Sidoarjo. PTA is the latest program specifically designed by the school to help students be more disciplined in praying in congregation, and giving more priority to prayer than other activities, in facing the challenges of this modern era. With this program, it is expected to form a generation that is not only academically intelligent, but also has strong moral and spiritual integrity. This research uses qualitative methods, with the subject of high school students Insan Cendekia Mandiri Sidoarjo. The data collection techniques used were interviews, observation, and documentation. The data obtained were analyzed using the Miles and Huberman model which includes three stages, namely data reduction, data presentation and conclusion drawing. The results of this study indicate that the discipline of congregational prayer through the Allah's Guest Servant program is able to improve student discipline. This is because the concept of discipline that emphasizes the growth of student self-awareness through the PTA program is not only focused on creating outward behavior, but more deeply by not relying on momentary punishment.